Tingkat Akurasi Nilai Atenuasi CT Scan Toraks sebagai Prediksi Analisis Cairan Pleura pada Pasien Efusi Pleura di Rumah Sakit Adam Malik Medan - Fiona Shafira Rosa; Netty Delvrita Lubis; Ade Rahmaini; Elvita Rahmi Daulay; Dedy Dwi Putra; Taufik Ashar (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Pleural effusion is a common clinical condition with diverse etiologies, making differentiation between transudative and exudative fluid essential. This differentiation is conventionally achieved through pleural fluid analysis via thoracentesis; however, the procedure is invasive and carries a risk of iatrogenic complications. Thoracic computed tomography (CT) may serve as a non-invasive alternative by assessing fluid density using Hounsfield Units (HU). This study aimed to evaluate the diagnostic accuracy of CT attenuation values in predicting pleural fluid characteristics in patients with pleural effusion at Adam Malik General Hospital, Medan. This correlational analytic study used an ambispective design based on medical records from January 2024 to November 2025. A total of 85 patients were included, comprising 57 exudative and 28 transudative effusions. Receiver operating characteristic (ROC) analysis demonstrated excellent discriminatory ability, with an area under the curve (AUC) of 0.954 (p < 0.001). The optimal cut-off value was 8.65 HU, yielding a sensitivity of 91.2% and specificity of 85.7% for identifying exudative effusion. CT attenuation values may serve as a useful non-invasive parameter in the initial evaluation of pleural effusion. However, they do not replace invasive procedures, which remain the diagnostic gold standard.